Penal Measures in the Light of the Amendment to the Penal Code Of July 7, 2022 – Selected Problems - Szeleszczuk, Damian (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The subject of the article are the changes regarding penal measures resulting from the amendment to the Penal Code and some other acts of July 7, 2022. They constitute a far-reaching interference in the system of penal measures. Basically, they aim at increasing the repressive nature of criminal law by extending the grounds for adjudicating these criminal policy instruments and by introducing solutions limiting the judgeʼs discretionary power (mandatory mode of adjudicating many criminal measures). The aim of the article is an attempt to evaluate the adopted solutions through the prism of political and criminal assumptions justifying the introduced changes and the criteria of rational law-making.